3D electrical resistivity tomography to locate DNAPL contamination around a housing estate. Issue 3 (1st November 2012) - Naudet, V.; Gourry, J.C.; Girard, F.; Mathieu, F.; Saada, A.
ABSTRACT: A 3D electrical resistivity survey is carried out downstream of a former coal refinery plant in France to determine the spatial extent of a DNAPL contaminant plume and to optimize the implantation of further boreholes. The site, which is located in the north of France, is the subject of an extensive conventional site investigation including the characterization of the contaminant source and natural attenuation monitoring of the plume. Previous geochemical and geophysical studies including 2D electrical resistivity profiles have shown a possible migration of the contaminant plume toward a housing estate, where no geochemical boreholes have been drilled. The purpose of this study was to achieve a real 3D imaging of the subsoil to locate the extent of the contaminant plume above the housing estate and determine the location of new boreholes. As geophysical measurements are difficult to perform in such an urban environment, a new electrical campaign was realized with innovative acquisition geometries and arrangement of surface electrodes in an L‐shape, disposing electrodes in lines around the housing estate. Data were inverted in 3D with ERTLab software from Multi‐Phase Technologies and Geostudi Astier. Results show a conductive plume emanating from old tar ponds and a slag heap that spreads through the housing estate. Based on these results, new boreholes were drilled in the housing estate, which confirm the extent of the contaminant plume estimated from the 3D electrical resistivity survey.